Electrophotocatalysis and Photocatalysis Methods By Using TiO2 For Decolorization of Remazol Red RB and Decreasing of Cd2+ Ion Concentration in Simultaneously - Anggraini, Riska Marina; Haris, M.Si, Drs. Abdul; Prasetya, S.Si, M.Sc., Nor Basid Adiwibawa (Chem Info Journal, 2013)
A study entitled Electrophotocatalysis and Photocatalysis Methods By Using TiO2 For Decolorization of Remazol Red RB and Decreasing of Cd2+ Ion Concentration Simultaneousy has been done. This study aimed to determine the effect of TiO2 photocatalyst of the decrease of Cd2+ and the effect of electrical potential on decolorization of Remazol Red RB and decrease of Cd2+ concentration simultaneously. TiO2/FTO was used as anode, on the other hand carbon was used as cathode, while the UV-C lamp was used as photon source. Electrophotocatalysis and photocatalysis were performed for 240 minutes. The final results were analyzed using UV-Vis Spectrophotometer for determining the absorbance of the Remazol Red RB remained and using Atomic Absorption Spectrophotometry (AAS) for determining Cd2+ remained. The results showed that the percentage of decolorization of dye solution containing Remazol Red RB and Cd2+ ion electrophotocatalysis and photocatalysis methods were 97.57% and 58.54% respectively, while the percentage of ion Cd2+ decrease by electrophotocatalysis and photocatalysis 84.7% and 76.3% respectively. Photocatalysis TiO2 by the addition of electric potential can minimize recombination of electron and hole pair that can decolorization Remazol Red RB and decrease Cd2+ ions concentration better than photocatalysis TiO2 without using addition of electric potential.